The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1051/0004-6361/201628821
|View full text |Cite
|
Sign up to set email alerts
|

Formation of S0 galaxies through mergers

Abstract: Context. Lenticular (S0) galaxies are known to derive from spiral galaxies. The fact that S0s nearly obey the Tully-Fisher relation (TFR) at z ∼ 0 (as spirals have done in the last ∼9 Gyr) is considered an argument against their major-merger origin because equal mergers of two disc galaxies produce remnants that are outliers of the TFR. Aims. We explore whether a scenario that combines an origin by mergers at z ∼ 1.8 − 1.5 with a subsequent passive evolution of the resulting S0 remnants since z ∼ 0.8-1 is comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 144 publications
4
38
1
Order By: Relevance
“…Given such a significant contribution to the stellar mass budget, persistent minor mergers could also explain how NGC 3115 transformed into an S0 galaxy, by building up the 'thick' disk and diluting any spiral arms that may have been present in the progenitor object. While previous works have claimed that either environmental perturbations (Bekki & Couch 2011), internal disk instabilities (Saha & Cortesi 2018), or major mergers (Querejeta et al 2015;Tapia et al 2017;Diaz et al 2018;Fraser-McKelvie et al 2018) are the likely formation paths for S0 morphologies, our model is inconsistent with these mechanisms. NGC 3115 is a field S0, making environmental perturbations unlikely, and both internal disk instabilities and major mergers would likely destroy the old disk structure that we find in our model.…”
Section: Implications For the Formation History Of Ngc 3115contrasting
confidence: 93%
“…Given such a significant contribution to the stellar mass budget, persistent minor mergers could also explain how NGC 3115 transformed into an S0 galaxy, by building up the 'thick' disk and diluting any spiral arms that may have been present in the progenitor object. While previous works have claimed that either environmental perturbations (Bekki & Couch 2011), internal disk instabilities (Saha & Cortesi 2018), or major mergers (Querejeta et al 2015;Tapia et al 2017;Diaz et al 2018;Fraser-McKelvie et al 2018) are the likely formation paths for S0 morphologies, our model is inconsistent with these mechanisms. NGC 3115 is a field S0, making environmental perturbations unlikely, and both internal disk instabilities and major mergers would likely destroy the old disk structure that we find in our model.…”
Section: Implications For the Formation History Of Ngc 3115contrasting
confidence: 93%
“…This paper was a proof of concept that major mergers can produce disc galaxies in the idealized scenario of two isolated galaxies, and allowed to study and follow in detail and in a controlled environment the formation of the disc. Similar work then followed, such as Tapia et al (2017), Eliche-Moral et al (2018) and Sauvaget et al (2018), who confirmed these results. However, such simulations are run in isolation, therefore they neglect the effect of the environment, and make assumptions on the parameters of the merger such as the orbit, or on the structures of the two merging galaxies.…”
Section: Introductionsupporting
confidence: 68%
“…Figure 1 illustrates the typical merger sequence, from initial approach (far left) to final coalescence (far right). These encounters lead to significant changes in stellar and gas morphology (e.g., Mihos 1995;Mihos et al 1995;Malin & Hadley 1997;Côté et al 1998;Knierman et al 2003;Lotz et al 2008;Wen & Zheng 2016;Tapia et al 2017), including the production of non-axisymmetric torques which enable gaseous inflows (e.g., Duc et al 2004;Blumenthal & Barnes 2018), which may feed the central black hole, producing heightened activity of the nucleus (e.g., Cutri & McAlary 1985;Dahari 1985;Heckman et al 1986a,b;Ellison et al 2011;Hewlett et al 2017;Trakhtenbrot et al 2017). Interacting and merging galaxies have been shown to host heightened rates of star formation (e.g., Joseph & Wright 1985;Kennicutt et al 1987;Whitmore & Schweizer 1995;Vigroux et al 1996;Mirabel et al 1998;Bridge et al 2007;Scudder et al 2012;Moreno et al 2015;Rich et al 2015;Moreno et al 2019).…”
Section: Introductionmentioning
confidence: 99%